CENSORSHIP, TECHNOLOGY, AND MORALITY IN RAY BRADBURY’S FAHRENHEIT 451 (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
Ray Bradbury’s Fahrenheit 451 presents a dystopian society dominated by censorship, advanced technology, and moral decline. This paper examines the interplay between technological control, societal censorship, and the preservation of human values. Using Montag’s experiences and his interactions with characters such as Faber and Millie, the study analyzes how the suppression of literature and critical thinking impacts individual morality and ethical consciousness. The analysis demonstrates that Bradbury warns against the dangers of unchallenged technological advancement and societal conformity, emphasizing the enduring significance of literature and human empathy.